Utilization of the Resistance of Some Leucaena Cultivars Against Leucaena - Psyllids for Forage Production : A Review - Sajimin, Sajimin (ANIMAL PRODUCTION, 2006)
Utilization of the resistance of some Leucaena cultivar of leucaena psyllids (Heteropsylla cubana). The degree of resistance was determined based on the  level  of  plant damage after a certain time of exposure to the psyllids and can  be  classified into three groups based on  their  levels  of damages.  They were : resistant (scale of 1 - 3) level  of  damage did  not  exceed curling of levels; tolerant (scale of  4  -  6) level of damage did not exceed 25% of leaf fall and susceptible (scale of 7 - 9) level damage exceed 75% of leaf fall.  Only one cultivar was highly resistant that was L. diversifolia at the field station.    There were positive corelations between psyllid counts correlated  with the levels of damage.  Nymphs of psyllid appeared to be  the main  cause of damage. Within the Leucaena genus L. diversifolia, Leucaena cv. Tarramba and Leucaena KX2 were psyllid-resistant and showing comparable agronomic  performance to L. leucocephala as alternative of forage availability for animal production. (Animal Production 8(2): 143-151 (2006) Key Words : Leucaena, resistant cultivars, Heteropsylla cubana